Mutational mechanism for DAB1 (ATTTC)n insertion in SCA37: ATTTT repeat lengthening and nucleotide substitution. Issue 4 (9th January 2019) - Loureiro, Joana R.; Oliveira, Cláudia L.; Mota, Carolina; Castro, Ana F.; Costa, Cristina; Loureiro, José L.; Coutinho, Paula; Martins, Sandra; Sequeiros, Jorge; Silveira, Isabel
Abstract: Dynamic mutations by microsatellite instability are the molecular basis of a growing number of neuromuscular and neurodegenerative diseases. Repetitive stretches in the human genome may drive pathogenicity, either by expansion above a given threshold, or by insertion of abnormal tracts in nonpathogenic polymorphic repetitive regions, as is the case in spinocerebellar ataxia type 37 (SCA37). We have recently established that this neurodegenerative disease is caused by an (ATTTC)n insertion within an (ATTTT)n in a noncoding region of DAB1 . We now investigated the mutational mechanism that originated the (ATTTC)n insertion within an ancestral (ATTTT)n . Approximately 3% of nonpathogenic (ATTTT)n alleles are interspersed by AT‐rich motifs, contrarily to mutant alleles that are composed of pure (ATTTT)n and (ATTTC)n stretches. Haplotype studies in unaffected chromosomes suggested that the primary mutational mechanism, leading to the (ATTTC)n insertion, was likely one or more T>C substitutions in an (ATTTT)n pure allele of approximately 200 repeats. Then, the (ATTTC)n expanded in size, originating a deleterious allele in DAB1 that leads to SCA37. This is likely the mutational mechanism in three similar (TTTCA)n insertions responsible for familial myoclonic epilepsy. Because (ATTTT)n tracts are frequent in the human genome, many loci could be at risk for this mutational process. Abstract : In DAB1, ∼3% of nonpathogenic (ATTTT)n alleles are interspersed by AT‐rich motifs, contrarily to mutant SCA37 alleles that are composed of pure (ATTTT)n and (ATTTC)n . Haplotype studies suggested that the mutational mechanism, leading to the (ATTTC)n insertion, was likely one or more T>C substitutions in an (ATTTT)∼200 . Then, the (ATTTC)n expanded, originating the SCA37 allele. This is likely the mutational mechanism in three (TTTCA)n insertions causing BAFME. Because (ATTTT)n are frequent, many loci could be at risk.